Rosário de lembranças: narrativas da festa de Nossa Senhora do Rosário (Milho Verde – MG) - Gilson Ferreira Silva (2019)
The work collected, from January 8 to 28, 2018, reports of four old protagonists and an old man of the party of Our Lady of the Rosary of the Black Men, in Milho Verde, Minas Gerais. In these testimonies are highlighted the continuities and ruptures existing in this feast, as well as the senses engendered in the praise of Our Lady. Inspired by the theoretical methodological guidelines of Oral History and some principles of documentary cinema, we realize that the narratives bring to light such elements as faith, belonging, songs, prayers, and constitutive memories of the festivities. The research also sought to contribute to heritage education in surrounding communities through the production of a documentary